2018
DOI: 10.3390/polym10010061
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation Polymerization Approach for Preparing Graphene/Polymer Composites

Abstract: Abstract:The rapid development of society has promoted increasing demand for various polymer materials. A large variety of efforts have been applied in order for graphene strengthened polymer composites to satisfy different requirements. Graphene/polymer composites synthesized by traditional strategies display some striking defects, like weak interfacial interaction and agglomeration of graphene, leading to poor improvement in performance. Furthermore, the creation of pre-prepared graphene while being necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 151 publications
(217 reference statements)
0
21
0
Order By: Relevance
“…It has been observed that the electrical, mechanical, and thermal properties of the polymeric material increased significantly by the addition of lesser amounts of these fillers to the polymer matrix. [1][2][3][4][5][6][7] Because of these properties, carbon-based polymer composites are used in various fields such as energy storage, energy conversion, flexible electronic materials, sensors, biomedical, and environmental. 4,6,[8][9][10][11] CNT and CM are carbon-based fillers with outstanding physicochemical properties and unique morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the electrical, mechanical, and thermal properties of the polymeric material increased significantly by the addition of lesser amounts of these fillers to the polymer matrix. [1][2][3][4][5][6][7] Because of these properties, carbon-based polymer composites are used in various fields such as energy storage, energy conversion, flexible electronic materials, sensors, biomedical, and environmental. 4,6,[8][9][10][11] CNT and CM are carbon-based fillers with outstanding physicochemical properties and unique morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that coating is well uniformed. In Figure 2d Raman spectrum of graphene oxide shows the presence of D and G bands at 1200-1300 cm -1 [25] and 1500-1600 cm -1 [26] respectively. D band occurs due to disordered structure of graphene while G band represents the graphitic nature.…”
Section: Resultsmentioning
confidence: 97%
“…Intercalation polymerisation has been extensively employed for preparing layered nanocomposites. 19,20 However, to the best of our knowledge, the use of this protocol to synthesise 2D polymers has not been reported. It is envisaged that a pathway similar to that shown in Figure 1c might occur, when biscyclopropene BCP-0 with a linker is employed (Figure 3a).…”
Section: Strategymentioning
confidence: 99%